Stage Design and Package Graphics in The Fifth 2024 Presidential Debate - Ma'mur, Angghi Muliya; Kurniawan, Fajar (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The General Election Commission of the Republic of Indonesia holds a Presidential Election every five years. The KPU holds a Presidential Candidate Debate as part of the Presidential Candidate Campaign. The KPU held a debate to provide space for voters to see directly the clear vision and mission of the presidential candidates. The KPU broadcasts the Presidential Candidate Debate live or directly via television broadcast. The KPU appointed a combination of television stations to hold the Presidential Candidate Debate 5 times. The TV station organizing the Debate must present the stage design and graphics for the Presidential Candidate debate to the KPU and Representatives of the Presidential Candidates. The time between debates is two weeks. Television stations require location setup preparation time of at least 3 or 4 days before Implementation. So, the design discussion process only takes five working days. This research uses qualitative methods, namely interviews and field observations, as well as primary and secondary data collection through searching library sources such as books, journals and media. Representatives of presidential candidates have a different view of stage design and graphic packages, namely, electorally. Representatives of the Presidential Candidates see this Debate as an opportunity to increase electability so that the display on the television screen does not disturb the viewer's concentration. So, the TV station organizers have to adjust the design.